2002
DOI: 10.1021/jf010968u
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Plasma with Olive Oil Phenols and Extracts:  Influence on LDL Oxidation

Abstract: Phenols present in olive oil may contribute to the health effects of the Mediterranean lifestyle. Olive oil antioxidants increase the resistance of low-density lipoproteins (LDL) against oxidation in vitro, but human intervention studies have failed to demonstrate similar consistent effects. To better mimic the in vivo situation, plasma was incubated with either individual olive oil phenols or olive oil extracts with different phenolic compositions, and LDL was subsequently isolated and challenged for its resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…In the context of the Mediterranean diet and coronary heart diseases, it has also been shown that VOO rich in phenols increases the resistance of LDL to oxidation, both in vitro and ex vivo [67][68][69]. The study carried out by Bogani et al [70] confirmed the anti-thrombotic and anti-inflammatory effects of VOO phenolic components, in a postprandial setting; in fact, the results showed significant reductions in serum concentration of inflammatory markers (TXB 2 and LTB 4 ) at 2 and 6 h after consumption of VOO, but not after consumption of either olive oil or corn oil.…”
Section: Health Aspects Linked To Phenols In Voomentioning
confidence: 99%
“…In the context of the Mediterranean diet and coronary heart diseases, it has also been shown that VOO rich in phenols increases the resistance of LDL to oxidation, both in vitro and ex vivo [67][68][69]. The study carried out by Bogani et al [70] confirmed the anti-thrombotic and anti-inflammatory effects of VOO phenolic components, in a postprandial setting; in fact, the results showed significant reductions in serum concentration of inflammatory markers (TXB 2 and LTB 4 ) at 2 and 6 h after consumption of VOO, but not after consumption of either olive oil or corn oil.…”
Section: Health Aspects Linked To Phenols In Voomentioning
confidence: 99%
“…However, this does not yet represent the total amount of effective olive oil phenols. Part of the phenols in olive oil are ligstrosideaglycones and tyrosol, which are mono-phenols (Figure 1) with little or no antioxidant capacity (Rice-Evans et al, 1996;Leenen et al, 2002). Of the six analysed Greek olive oils, the mean percentage of diphenols was 44 mol% (range 39-51 mol%).…”
Section: Chemistry and Content Of Phenols In Olive Oilmentioning
confidence: 99%
“…The daily intake, bioavailability, and the amount of hydroxyl groups per molecule, and thus the antioxidant potential (Rice-Evans et al, 1996;Leenen et al, 2002), differ among various types of phenols. Therefore, it is difficult to compare the antioxidant effect of olive oil phenols in vivo with that of phenols from other foods, like wine, coffee, tea, onions, or apples.…”
Section: Are Phenols Antioxidants In Vivo?mentioning
confidence: 99%
See 1 more Smart Citation
“…A diet rich in unsaturated fatty acids from olive oil reduces waist girth, a significant indicator of metabolic disease, in addition to reducing body mass index (40). In addition, a study supports the hypothesis that extra virgin olive oil phenols protect low density lipoproteins in the plasma against oxidation (41).…”
Section: Discussionmentioning
confidence: 56%